Software patents don't compute no clear boundary between math and software exists. - Klemens, B. (IEEE spectrum)
This paper discusses the current debate on how software patents should be granted. While US laws state that scientific principles and mathematical algorithms may not be patented, mathematics has become increasingly reliant on machines. Because of the machine-intensiveness of modern mathematics and the math-intensiveness of modern machines, the line between mathematical algorithms and machinery has become increasingly blurred. This becomes a problem because without a clear line delimiting what is patentable and what is not, creative entrepreneurs will eventually be able to claim sole ownership of abstract mathematical discoveries.